2014
DOI: 10.1111/mmi.12811
|View full text |Cite
|
Sign up to set email alerts
|

A CaulobacterMreB mutant with irregular cell shape exhibits compensatory widening to maintain a preferred surface area to volume ratio

Abstract: Summary Rod-shaped bacteria typically elongate at a uniform width. To investigate the genetic and physiological determinants involved in this process, we studied a mutation in the morphogenetic protein MreB in Caulobacter crescentus that gives rise to cells with a variable-width phenotype, where cells have regions that are both thinner and wider than wild-type. During growth, individual cells develop a balance of wide and thin regions, and mutant MreB dynamically localizes to poles and thin regions. Surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…For example, E. coli and other bacteria are known to modulate their average length in response to nutrient availability and cell density (Akerlund et al, 1995; Schaechter et al, 1958). Using high-precision image analysis software (Sliusarenko et al, 2011), we found that while the cell width slightly varies (Harris et al, 2014), the length of asymmetrically dividing C. crescentus appears insensitive to environmental fluctuations. There was no discernable difference in cell length distributions between C. crescentus populations grown in nutrient-poor (M2G) or nutrient-rich (PYE) medium (Figure 1B), despite significant differences in growth rates, with doubling times of 146 ± 5 min in M2G (mean ± SD, n = 2 experiments) and 96 ± 1 min in PYE ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…For example, E. coli and other bacteria are known to modulate their average length in response to nutrient availability and cell density (Akerlund et al, 1995; Schaechter et al, 1958). Using high-precision image analysis software (Sliusarenko et al, 2011), we found that while the cell width slightly varies (Harris et al, 2014), the length of asymmetrically dividing C. crescentus appears insensitive to environmental fluctuations. There was no discernable difference in cell length distributions between C. crescentus populations grown in nutrient-poor (M2G) or nutrient-rich (PYE) medium (Figure 1B), despite significant differences in growth rates, with doubling times of 146 ± 5 min in M2G (mean ± SD, n = 2 experiments) and 96 ± 1 min in PYE ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that individual Caulobacter crescentus cells move toward and maintain a target SA/V over time, even changing their radius when necessary (Harris et al, 2014). Here, we develop a model for SA/V determination that could explain this ability of cells to adopt a steady-state SA/V over time without the need to invoke a specific SA/V sensing system.…”
Section: Resultsmentioning
confidence: 99%
“…However, as with length, the fluid modulation of cell width in response to changing physiological conditions (Volkmer and Heinemann, 2011) implies that genetic control cannot be the only force at play. Indeed, when we analyzed the growth patterns of an MreB mutant with a variable-width phenotype (Harris et al, 2014), we found that cell surface area to volume ratio (SA/V) was still conserved; cells modified their width in order to achieve and maintain a specific, condition-dependent SA/V, suggesting that attaining a target SA/V could lie upstream of width determination.…”
Section: Introductionmentioning
confidence: 99%
“…Two concepts have gained experimental support recently for regulating Caulobacter cell size and shape: (i) length homeostasis through “adder” or “mixer” mechanisms [101,102] and (ii) maintenance of a constant surface area to volume ratio under a given physiological condition [103,104]. The adder principle states that bacterial cells, including Caulobacter , achieve cell length homeostasis by growing a relatively constant amount prior to each cell division, regardless of length at birth [101].…”
Section: Shape Rules: Quantitative Principles Governing Cell Size Andmentioning
confidence: 99%